Improving Student Learning Outcomes through the Application of Problem Based Learning Models in Fiqh Lessons on Tharah - Muhdi; Muhammad Yuzril Syamsu Ardhy (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to Improve Student Learning Outcomes Through the Application of Problem Based Learning Models in Fiqh Lessons About THARAH. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were grade VII students of MTs Manba'ul Hikmah. The data for this study were obtained using test, observation and documentation techniques. Tests are used to determine students' understanding after the action, while observations are used to determine the activities carried out by teachers in taking actions and students in following the learning process in class. While documentation is used to obtain data on student grades and photos of the implementation of classroom actions. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study show that 1) The use of the PBL learning model in the learning process of THARAH material has an impact on increasing student understanding. 2) The use of the PBL learning model in the learning process of THARAH material can improve student learning outcomes, this is evidenced by the following data: Initial conditions, the percentage of creative thinking ability is 33.4%, the average score is 58.6. The percentage of learning outcomes is 70%, the average is 71.5, the highest score is 85 and the lowest is 67. The current condition of the percentage of creative thinking ability is 51.8%, the average score is 79.51. The percentage of learning outcomes is 76.65%, the average is 78.8, the highest score is 88 and the lowest is 70.